2013
DOI: 10.1016/j.neuroimage.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Variation in longitudinal trajectories of regional brain volumes of healthy men and women (ages 10 to 85years) measured with atlas-based parcellation of MRI

Abstract: Numerous cross-sectional MRI studies have characterized age-related differences in regional brain volumes that differ with structure and tissue type. The extent to which cross-sectional assumptions about change are accurate depictions of actual longitudinal measurement remains controversial. Even longitudinal studies can be limited by the age range of participants, sex distribution of the samples, and scan intervals. To address these issues, we calculated trajectories of regional brain volume changes from T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
202
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 224 publications
(247 citation statements)
references
References 107 publications
38
202
3
1
Order By: Relevance
“…Similar results were previously observed (Fjell et al, 2009;Fjell et al, 2013;Goodro et al, 2012;Pfefferbaum et al, 2013;Walhovd et al, 2011). Goodro and colleagues suggested that periventricular white matter signal hyperintensities, which is highly correlated with age, could be responsible for this increase of caudate volume, from the age of 60 onward.…”
Section: Effect Of Agesupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were previously observed (Fjell et al, 2009;Fjell et al, 2013;Goodro et al, 2012;Pfefferbaum et al, 2013;Walhovd et al, 2011). Goodro and colleagues suggested that periventricular white matter signal hyperintensities, which is highly correlated with age, could be responsible for this increase of caudate volume, from the age of 60 onward.…”
Section: Effect Of Agesupporting
confidence: 84%
“…Indeed, although many studies have described the influence of age and sex on brain volumes (Fjell et al, 2013;Luders et al, 2009;Pfefferbaum et al, 2013;Walhovd et al, 2011), very few attempts have been made to produce proper neuroanatomical volumetric normative data (Brain Development Cooperative Group, 2012;Kruggel, 2006). The many obstacles inherent to neuroimaging research likely undermine this shortcoming.…”
Section: Introductionmentioning
confidence: 99%
“…Age is an additional factor that leads to brain tissue volume decline in humans (Pfefferbaum et al, 1994;Pfefferbaum et al, 2013;Raz et al, 2010;Raz et al, 2005). The animals studied here ranged in age from 5.5 to 9.6 years at the beginning of the induction period, with a mean ± SD of 7.2 ± 1.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…On balance, existing research is consistent with these hypotheses, with frontal and heteromodal association areas most commonly identified as undergoing more rapid decline than sensory-motor regions [16,19,21,25,39]. This leads directly to the conclusion that accelerated volume loss is not simply a global feature of structural brain aging.…”
Section: Global and Regional Changesmentioning
confidence: 92%
“…Finally, while a full review of sex differences in age-related brain change is beyond the scope of this review, it is important to note that the majority of published reports (whether cross-sectional or longitudinal) and across both global and regional measures, show a steeper and more rapid trajectory of decline for males than females [e.g. 3,19,20,24,[25][26][27] Regional changes. The earliest in vivo imaging studies reported global, or non-specific, brain changes in late life [28].…”
Section: Global and Regional Changesmentioning
confidence: 99%